The Difference Between Male and Female Language Style of Students Grade VIII - Firinta Togatorop; Doris Yolanda Saragih (Departement of Mathematics Education, 2023)
This research is about sociolinguistics specified on the difference between male and female language style of students grade VIII in SMP Negeri 1 Pematangsiantar. This research focuses on the problems about: (1) Whatlanguage style are used by male students of grade VIII in SMP Negeri 1 Pematangsiantar (2) What language style are used by female students of grade VIII in SMP Negeri 1 Pematangsiantar (3) What are the differences between male and female students language style at grade VIII in SMP Negeri 1 Pematangsiantar. To answer the problems of this research, the writer uses related theory such as, Chaika (1982), Broderick (1976), Keraf (1984), Leech (2006), Maleong (2007). This research applies descriptive qualitative research, aimed at describing language style of eight grade students of SMP Negeri 1 Pematangsiantar. The subject of this research are 30 students, consists of 14 male students and 16 female students. The data was collected by observation and recording. The method covers research design, the subject, the object, the instrument, the technique of collecting data and the technique of analyzing data. The result of this research shows that (1) The writer found two language styles used by male students. (2) The writer found three language styles used by female students. (3) The difference language style between male and female students stated that intimate style used by female students but male students didn’t use intimate language style. Finally, from the result of the data analysis, the writer found that every student has different language style. Male and female students of SMP Negeri 1 Pematangsiantar used three types of language style from five language style. Formal and casual style used by male students while, formal, casual and intimate style used by female students.